2021
DOI: 10.3389/fimmu.2021.652470
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in COVID-19

Abstract: Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathophysiology, particularly in those with severe disease courses. While originally considered to be a rather homogeneous cell type, recent attention to neutrophils has uncovered their fascinating transcriptional and functional diversity as well as their developmental trajectories. These new findings are important to better understand the many facets of neutrophil involvement not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
239
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(272 citation statements)
references
References 109 publications
27
239
0
6
Order By: Relevance
“…Similarly, Patel noted that the test results presented in various studies of COVID-19 children were mostly within the reference range used for that particular study [24]. Interestingly, this is contrary to expected lymphopenia, and an elevated neutrophil-tolymphocyte ratio has emerged as a characteristic feature of severe COVID-19 [35], probably because of the predominantly milder form of the disease in children.…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, Patel noted that the test results presented in various studies of COVID-19 children were mostly within the reference range used for that particular study [24]. Interestingly, this is contrary to expected lymphopenia, and an elevated neutrophil-tolymphocyte ratio has emerged as a characteristic feature of severe COVID-19 [35], probably because of the predominantly milder form of the disease in children.…”
Section: Resultsmentioning
confidence: 90%
“…The study demonstrated the existence of 35 species with different susceptibility profiles to antifungal drugs and a predisposition to patients who are immunocompromised or have received prior antifungal therapy [9] . COVID-19 has been found to cause immune dysregulation and hyperinflammation in severe cases potentially contributing to the development of nosocomial infections in severely ill patients [10] , [11] , [12] . Nevertheless, limited data regarding bacterial and fungal infections in COVID-19 patients has been published [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the immune response to COVID-19 is complex. Neutrophils in the nasopharyngeal epithelium demonstrate markers of premature activation, 11 while the cells of adaptive immunity (T cells, NK cells, and B cells) are reduced in numbers. 12 These abnormalities tend to peak in the second week, which may explain the clustering of cases of CAM in the third week after COVID-19 symptom onset.…”
Section: Immune System Modulation Due To Covid-19 Diabetes and Steroidsmentioning
confidence: 99%